Antifilarial activity of the extract of leaves of Mimusops elengi Linn. on Setaria cervi in vitro - Ahmed, Qamar Uddin; Khan, Nizam Ud Din; Singhal, Kavita C. (2004)
Effect of aqueous and alcoholic extracts of the leaves of Mimusops elengi Linn. on the spontaneous movements of both the whole worm, the split preparation of Setaria cervi and on the survival of microfilariae in vitro was studied. Alcoholic extract of leaves caused inhibition of the spontaneous movements of the whole worm and the split preparation of S. cervi, while aqueous extract did not show any effect. The initial stimulatory effect was not observed by alcoholic extract of leaves on the spontaneous movements of whole worm as well as split preparation. The concentrations required to inhibit the movements of the whole worm and split preparation for alcoholic extract of leaves were 280 and 40 mg/ml, respectively, suggesting a cuticular permeability barrier. Alcoholic extract of leaves caused death of microfilariae in vitro. LC50 and LC90 were 15 and 25 ng/ml, respectively for alcoholic extract of leaves.